2014
DOI: 10.2337/db13-1785
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping and Functional Studies of Risk Variants for Type 1 Diabetes at Chromosome 16p13.13

Abstract: Single nucleotide polymorphisms (SNPs) located in the chromosomal region 16p13.13 have been previously associated with risk for several autoimmune diseases, including type 1 diabetes. To identify and localize specific risk variants for type 1 diabetes in this region and understand the mechanism of their action, we resequenced a 455-kb region in type 1 diabetic patients and unaffected control subjects, identifying 93 novel variants. A panel of 939 SNPs that included 46 of these novel variants was genotyped in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
(49 reference statements)
1
20
0
Order By: Relevance
“…We have also demonstrated that increased T1D risk mediated through 16p13.13 is associated with decreased DEXI expression, implying that wild-type or normal DEXI function has a protective function in autoimmune disease (25). Our eQTL result has since been replicated by other groups (24,26), but in the absence of a Dexi knockout mouse model, definitive studies to extend evidence in support of DEXI's preventive role in T1D have not been possible. Furthermore, there are so far no known rare variants of DEXI in humans with informative phenotypes.…”
Section: Main Text: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…We have also demonstrated that increased T1D risk mediated through 16p13.13 is associated with decreased DEXI expression, implying that wild-type or normal DEXI function has a protective function in autoimmune disease (25). Our eQTL result has since been replicated by other groups (24,26), but in the absence of a Dexi knockout mouse model, definitive studies to extend evidence in support of DEXI's preventive role in T1D have not been possible. Furthermore, there are so far no known rare variants of DEXI in humans with informative phenotypes.…”
Section: Main Text: Introductionmentioning
confidence: 78%
“…Within the complex 16p13.13 region, most studies have focussed upon the function of CLEC16A itself because the most associated SNPs are located in intron 19 of the gene (18)(19)(20)(21)(22)(23)(24). However, we have identified DEXI as a causal candidate gene in the 16p13.13 region our previous work, using expression quantitative trait locus (eQTL) mapping and chromosome confirmation capture (3C) in human monocytes.…”
Section: Main Text: Introductionmentioning
confidence: 99%
“…Recent work has focused on pathway analysis as well as functional studies of the variants identified [35, 11••, 36, 10, 37, 38•]. Most of the variants identified to date are non-coding SNPs.…”
Section: Genes Implicated In Gwas Of T1dmmentioning
confidence: 99%
“…It is important to note, in the context of complex and not-entirely understood regulation of gene expression, that the genes implicated are not necessarily the most proximal gene to each SNP In addition to GWAS, several techniques have been used implicate specific genes; e.g., survey of expression quantitative trait loci or interrogation of chromatin state. Within immune-related genes, the function of the variants is mostly still not entirely understood, but the genes implicated can be broadly divided into (a) genes involved in innate immunity (e.g., IFIH1 and CLEC16A ), (b) genes altering the strength of receptor signaling (e.g., PTPN22, PTPN2 and SH2B3 ), (c) genes altering the balance between immunity and tolerance, often via alteration of IL-2 signaling (e.g., IL-2, IL2RA , and PTPN2 ) and (d) other genes [10, 39, 29, 4042]. …”
Section: Genes Implicated In Gwas Of T1dmmentioning
confidence: 99%
See 1 more Smart Citation